CMyc-p53 feedback mechanism regulates the dynamics of T lymphocytes in the immune response. Issue 9 (2nd May 2016) - Madapura, Harsha S.; Salamon, Daniel; Wiman, Klas G.; Lain, Sonia; Klein, Eva; Nagy, Noémi
ABSTRACT: Activation and proliferation of T cells are tightly regulated during the immune response. We show here that kinetics of proliferation of PHA activated T cells follows the expression of cMyc. Expression of p53 is also elevated and remains high several days after activation. To investigate the role of p53 in activated T cells, its expression was further elevated with nultin-3 treatment, a small molecule that dissociates the E3 ubiquitin protein ligase MDM2 from p53. Concomitantly, cMyc expression and proliferation decreased. At the other end of the cMyc-p53 axis, inhibition of cMyc with 10058-F4 led to down regulation of p53, likely through the lower level of cMyc induced p14ARF, which is also known to dissociate the p53-MDM2 complex. Both compounds induced cell cycle arrest and apoptosis. We conclude that the feedback regulation between cMyc and p53 is important for the T cell homeostasis. We also show that the two compounds modulating p53 and cMyc levels inhibited proliferation without abolishing the cytotoxic function, thus demonstrating the dichotomy between proliferation and cytotoxicity in activated T cells.